Spatial distribution maps for tourist sites in Babil Governorate using GIS and RS remote sensing (Journal of the College of Basic Education, 2022)
The spatial distribution maps based on applied geographical studies that have become after my place and with the help of GIS and remote sensing, became characterized by high spatial precision, and are one of the means of spatial analysis and analysis of spatial relationships, and give a clear picture of all tourist sites and tourist services and projects of tourism development.I search in four sections it came, and emerged from the research problem (What are the methods of cartography appropriate for the distribution and representation of tourist sites in the study area? And the nature of the spatial distribution of tourist sites in the study area?) Which sought to achieve a number of goals, namely the preparation of accurate tourist maps high spatial containing tourist attractions, the distribution of tourist sites, and give the about, build a tourist database, which includes all data related to tourism sites and their characteristics, and using geographic information systems applications. The study dealt with the maps of spatial analysis and divided the study area into regions according to the density of religious, archeological, and heritage sites, and then methods standard distances and real decomposition of the Mediterranean and central sites, and concluded with some conclusions, including that maps give a realistic picture of indicators and spatial development of tourist sites, and the use of geographic information systems and remote sensing p After preparing features tourist maps characterized by high spatial precision.